Determination of the Relationship Between Problematic Mobile Phone Use and Communication Skills Together with Social Support - Kılınç, Nur Özlem; Türkoğlu, Nihan (My University, 2021)
Objective: This is a descriptive and cross-sectional study conducted to assess the relationship between problematic mobile phone use of nursing students and their communication skills together with social support levels. Methods: The population of the study was created by 210 students enrolled at the faculty of health sci-ences of a university in the east of Turkey, and the sample was created by 190 persons who volunteered to participate in the study and who were continuing their education during the date of the study. “Descriptive Information Form,” “Problematic Mobile Phone Use Scale,” and “Assessment of Communication Skills Scale” were used in the collection of data. Results: Mean score from problematic mobile phone use of students that participated in the study was determined as 28.64 ± 8.96 while their mean communication skills score was determined as 75.28 ± 10.88. The negative relationship was determined between Problematic Mobile Phone Use and Communication Skills Assessment, and a statistically significant decrease was established in the score received from the communication skills assessment scale as problematic mobile phone use increased (P <.001). Conclusion: As problematic the use of mobile phone that is used by all of the students participating in the study increases, the communication skills decrease. © 2021, Istanbul Universitesi. All rights reserved.
Cep Telefonu Problemli Kullanımı ile İletişim Becerileri ve Sosyal Destek Arasındaki İlişkinin Belirlenmesi
Keywords: communication; mobile phone; nursing; problematic use; social support